Flow Shears at the Poleward Boundary of Omega Bands Observed During Conjunctions of Swarm and THEMIS ASI. Issue 3 (6th February 2018) - Liu, Jiang; Lyons, L. R.; Archer, W. E.; Gallardo‐Lacourt, B.; Nishimura, Y.; Zou, Ying; Gabrielse, C.; Weygand, J. M.
Abstract: Omega bands are curved aurora forms that evolve from a quiet arc located along the poleward edge of a diffuse auroral band within the midnight to morningside auroral oval. They usually propagate eastward. Because omega bands are a significant contributor to an active magnetotail, knowledge about their generation is important for understanding tail dynamics. Previous studies have shown that auroral streamers, footprints of fast flows in the tail, can propagate into omega bands. Such events, however, are limited, and it is still unclear whether and how the flows trigger the bands. The ionospheric flows associated with omega bands may provide valuable information on the driving mechanisms of the bands. We examine these flows taking advantage of the conjunctions between the Swarm spacecraft and Time History of Events and Macroscale Interactions during Substorms all‐sky imagers, which allow us to demonstrate the relative location of the flows to the omega bands' bright arcs for the first time. We find that a strong eastward ionospheric flow is consistently present immediately poleward of the omega band's bright arc, resulting in a sharp flow shear near the poleward boundary of the band. This ionospheric flow shear should correspond to a flow shear near the inner edge of the plasma sheet. This plasma sheet shear may drive a Kelvin‐Helmholz instability which then distorts the quiet arc to form omega bands. It seems plausible that the strong eastward flows are driven by streamer‐related fast flows or enhanced convection in the magnetotail. Plain Language Summary: Near the Arctic Circle, people often see Ω‐shaped aurorae. These aurorae are indicators of dynamic activities in Earth's magnetosphere. Therefore, knowledge about how the Ω‐shaped aurorae are generated is important for understanding the magnetospheric dynamics. In this study, we explore the possible driver of these aurorae by observing plasma flows near the aurorae. We found that a flow shear exist at the boundary of the Ω‐shaped aurora. This finding implies that an enhanced flow in the magnetosphere drives the Ω‐shaped aurorae by triggering plasma instabilities. Key Points: An ionospheric flow shear exists near the poleward boundary of the omega band arc and leads to an eastward flow peak poleward of the arc The flow shear is located near the boundary separating region 1 and region 2 currents and maps to a nightside L shell of 6‐11 The flow shear may drive the omega band via Kelvin‐Helmholz instabilities